Epitaxial growth and characterization of approximately 300-nm-thick AlInN films nearly lattice-matched to c-plane GaN grown on sapphire. (5th April 2018) - Miyoshi, Makoto; Yamanaka, Mizuki; Egawa, Takashi; Takeuchi, Tetsuya
Abstract: AlInN epitaxial films with film thicknesses up to approximately 300 nm were grown nearly lattice-matched to a c -plane GaN-on-sapphire template by metalorganic chemical vapor deposition. The AlInN films showed relative good crystal qualities and flat surfaces, despite the existence of surface pits connected to dislocations in the underlying GaN film. The refractive index derived in this study agreed well with a previously reported result obtained over the whole visible wavelength region. The extinction coefficient spectrum exhibited a clear absorption edge, and the bandgap energy for AlInN nearly lattice-matched to GaN was determined to be approximately 4.0 eV.